Earth apples the poetry of Edward Abbey = Pommes de terre - Abbey, Edward 1927-1989 (St. Martin's Press, 1994)
The title, a direct translation of the French pommes de terre-p̓otatoes--reflects the author's plain-speaking approach to poetry: he loves wild doves, hates New York and is fond of bawdy women. Original art work.
Keywords: Abbey, Edward <1927-1989> -- Poems; Geschichte 1900-2000; American poetry -- 20th century